Recruiting Adolescents from Medicaid Enrollment Files into a Neighborhood Oral Health Study - Basson, A A; Yoo, M; Chi, D L (JDR clinical and translational research, 2019)
Strategies are needed to improve recruitment of low-income adolescents into oral health studies. In this study, we assessed the feasibility of recruiting Medicaid-enrolled adolescents into a neighborhood-level oral health study using Medicaid enrollment files and to evaluate the degree of bias in the final recruited study population. We obtained Medicaid enrollment files from the Oregon Health Authority for 15,440 Medicaid enrollees aged 12 to 17 y from Multnomah, Hood River, and Tillamook counties. We attempted to contact the primary caregiver of each adolescent by telephone, and we tracked contact, recruitment, enrollment, and study completion rates. We further assessed if these rates were different across county-level rurality, neighborhood-level income, and caregiver-level language preference (Spanish vs. English). The Pearson chi-square test was used to compare rates (α = 0.05). We contacted 6,202 caregivers (40.2%), recruited 738 adolescents (11.9%), enrolled 335 (45.4%), and had complete data for 284 (84.8%). The overall enrollment yield from contacted caregivers was 5.4%. Contact rates did not differ significantly by rurality ( = 0.897), but they were significantly lower in the lowest-income neighborhoods ( = 0.023). Recruitment rates were significantly higher for adolescents from rural counties ( = 0.001), but they did not differ by income or language preference. Enrollment rates were significantly higher among adolescents from rural counties ( < 0.001) and were significantly associated with income ( = 0.041), but they were not different by language preference ( = 0.083). Among participants with complete data, there were no differences by rurality or income, but a significantly larger proportion of adolescents with complete data had caregivers with a language preference for Spanish ( = 0.043). It is feasible to recruit Medicaid-enrolled adolescents into a neighborhood oral health study through the use of Medicaid files. County-, neighborhood-, and caregiver-level factors may influence characteristics of the final study population. Additional research is needed to improve recruitment of Medicaid enrollees into neighborhood oral health studies. Researchers can use the results of this study to plan neighborhood-level oral health studies involving recruitment of low-income adolescents. Findings further underscore the importance of assessing factors related to recruitment to evaluate participant bias and the generalizability of study findings.